Pharmacokinetics of Doxycycline and Tissue Concentrations of an Experimental Long-acting Parenteral Formulation of Doxycycline in Wistar Rats - Vargas-Estrada, Dinorah; Gutiérrez, Lilia; Juarez-Rodríguez, Ivan; Sumano, Héctor (Arzneimittelforschung, 2008)
Doxycycline hyclate (CAS 24390-14-5, doxycycline-h), an antibacterial with time-dependent action, was formulated as a non-irritating long-acting parenteral formulation based on a β-cyclodextrin: poloxamer-based matrix (doxycycline-h-LA). Tissue and serum concentrations vs time profile were investigated after its subcutaneous injection to Wistar rats. Serum concentration profiles and key pharmacokinetic (PK) variables of doxycycline-h-LA were compared to the corresponding profiles and PK values obtained with an aqueous formulation of doxycycline-h administered either intramuscularly, orally or intravenously to Wistar rats. In all groups, the dose was 10 mg/kg. Doxycycline-h-LA showed outstanding bioavailability (951% or 477% if a correction formula is considered), as compared to the one obtained with an aqueous formulation (106-82%, respectively). Corresponding values for maximum serum concentration were 3.19 µg/ml and 3.00 µg/ml, respectively, and elimination half-lives were completely different: 42.49 h and 2.77 h for doxycycline-h-LA and the aqueous formulation, respectively. Considering minimal inhibitory concentrations of doxycycline for sensitive and resistant bacteria (from ≤ 0.5 to ≥1.5 µg/ml), doxycycline-h-LA could be injected every 2 or 3 days, while aqueous doxycycline-h would require a dosing interval from 7.5 to 11 h. But if tissue concentrations are taken as braking points, the dosing interval will vary from 48 to 94 h. For doxycycline-h-LA, mean tissue:serum ratios were 2:1 for lungs, 9.8:1 for kidneys and 2.2:1 for intestine homogenates. These values are in close agreement with those found for the distribution of doxycycline in other species.
Keywords: Antibacterials; CAS 24390-14-5; Doxycycline, pharmacokinetics, rat, sustained-release